Shifting paradigms of globalization: The twenty-first century transition towards generics in skilled migration from India - Khadria, Binod [Verfasser] (My University, 2001)
"Globalization of human capital through international migration is no longer about global physical presence only; it is also about global applicability of skills across various fields of specialization. This marks the main characteristics of skilled migration from India to developed countries in the twenty-first century. The focus is shifting away from professionals in specific occupations, like doctors, engineers, scientists, architects, bankers, to information technology (IT) professionals embodying, in a way, more generic skills. In other words, it is the generic applicability of information and communications technology (ICT) which has led to large-scale migration of Indians skilled in IT. Moreover, the exodus comprises not only the fully trained and educated workers going abroad for employment, but also students - the semi-finished human capital - pursuing higher education in onshore as well as offshore universities of the developed countries. The new emigration is directed towards traditional host countries in the West such as the UK, Canada, and the US, but also towards newly emerging destinations in continental Europe (Germany, France, Belgium, Italy, Denmark), Australasia (Australia, New Zealand), East Asia (Japan, Republic of Korea), and South-East Asia (Singapore, Malaysia). By using mainly current information and informal data as reported in the media, this article perceives emerging trends and changes in the context of the global labour market for skills, and suggests a possible framework towards evolving strategies of remedial development." (author's abstract, IAB-Doku) ((en))
Keywords: G 2.1.3 Internationale Arbeitsteilung; G 1.3.3.3 Mobilität; G 1.1.1 Demografie; G 2.1 Globalisierung; I 2.3.4 Asien; Hochqualifizierter; Internationale Wanderung; Arbeitskräftemobilität; Brain drain; IT-Beruf; Globalisierung; Quantitative Angaben; Indien; 1999-2000; Industrieländer